Associated Field Semantics in Modeling Lesya Ukrainka’s Image - Bohdan, Svitlana; Tarasiuk, Tetiana (East European Journal of Psycholinguistics, 2020)
The article is focused on the study of the perception of Lesya Ukrainka, a famous Ukrainian writer, in contemporary Ukrainian society. The research is based on a free word association test held online with 200 respondents aged from 13 to 70. As a result of applying quantitative analysis of the associates and semantic gestalt method the authors singled out productive semantic zones concerning each of the stimuli. These zones presented an anthroponymic triad of personality identification related to the author’s names ‘Larysa Kvitka’, ‘Larysa Kosach’, and the pseudonym ‘Lesya Ukrainka’. The nuclear zones in each associative field manifest a tendency for uniformity. They are related to her professional activities, her works, elements of inner and outer portrayal, as well as of evaluative spectrum. The respondents have shown predominantly high levels of knowledge about Lesya Ukrainka’s personality, which is proven, in particular, by their reverse frequency reactions and peripheral character of zero reactions. A dominant positive evaluative spectrum of perception of Lesya Ukrainka, as well as productivity of individual associates of interpretational character, was also important.